Use of marketplace waste products (polysaccharide from squids'skin) to reduce cattle enteric methane emissions in vitro - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
An in vitro gas production experiment (proof of concept) with different concentrations of Chitosan and Naringin was performed. Significant reduction in methane production was observed in vitro. Next phase in this topic (on going) is on validating this new discovery on farm under grazing conditions.